Referee Bias - Thomas Dohmen; Jan Sauermann (Institute for the Study of Labor (IZA), 2015)
This paper surveys the empirical literature on the behavior of referees in professional football and other sports. Referees are typically appointed by a principal to be impartial, especially when unbiased referee judgment is vital for the accomplishment of the principal's objective. Answering whether referees make biased decisions and understanding the causes that lead referees to digress from their principal duty of impartiality is therefore fundamental from a theoretical point of view. At the same time, assessing the prevalence and origin of referee bias is germane to various domains of life. Referee bias is particularly relevant in sports, where partial decision-making can determine competition outcomes, which can have strong repercussions on athletes' careers and supporters' well-being.
Keywords: D8; L83; 330; favoritism; referee bias; social pressure